Perception of the forest by the villagers of the Salonga National Park in the Democratic Republic of Congo - J. M. Ibesoa (Journal of Forest Science, 2009)
Effective forest management demands detailed knowledge of resources. Local forest users are usually the best source of information. In the Democratic Republic of Congo forest management partnerships between local people and government staff have become more common. A proper understanding of local perceptions of the forest is needed. This study was designed and guided by a multidisciplinary team including a sociologist, a linguist and a forester. It identified and compared classification and management units. It also touched on the different uses of the forest products, the species that provided these products and the locations of these species.